Diseño de una máquina compactadora de carrocerías de carros y camionetas (2017)
In this project was realized with the purpose of optimizing the space used in the containers, reducing the volume that occupy the bodies of cars and vans, reducing costs and times of operation and reducing the possibilities of labor risk for the strategic unit of CESVI Repuestos. In the first instance, different forms of compaction were defined, through three proposed alternatives, which were evaluated, and then select the one with the design that best meets the requirements of CESVI Repuestos and complying with the established parameters. A detailed design was performed in which the systems, components and structure of the compacting machine were calculated; This design was evaluated by finite element analysis using the NX 9.0 software, thus confirming the calculations mentioned. After obtaining the specifications of the different components of the compacting machine, systems, materials and dimensions, the plans of the compaction machine were developed and the plan of manual maintenance of operation and manual of assembly was elaborated. Finally, the financial evaluation and environmental impact study was carried out for the production of the compacting machine.